Sanksi Pidana Pencemaran Nama Baik Dimedia Sosial Berdasarkan Undang-Undang Informasi dan Transaksi Elektronik (Studi Putusan Pengadilan Negeri Nomor : 259/Pid.Sus/2019/PN Bir) - Sapto Budoyo; Praditya Arcy Pratama; Nia Yunita Sari (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The rampant use of technology at this time has caused various changes that have a major impact on society, one of which is the use of social media related to freedom of expression and opinion. So that someone can easily provoke and defame others. The purpose of this study is to find out the factors a person commits a criminal act of defamation on social media and to find out an analysis of criminal sanctions for defamation on social media. The research was conducted using normative juridical methods. The results of this study indicate that someone commits a criminal act of defamation on social media due to internal factors, namely hurt, while external factors such as human resources, namely the social environment, economy, politics, low level of education, lack of legal awareness. The judge's decision is in accordance with the legal provisions based on Article 27 paragraph (3) juncto Article 45 paragraph (3) of the Law of the Republic of Indonesia Number 19 of 2016 on amendments to Law Number 11 of 2008 regarding information and electronic transactions.